Nanogels Based on Hyaluronic Acid as Potential Active Carriers for Dermatological and Cosmetic Applications - Emanuele Mauri; Stefano Scialla (2023)
Nanogels are a prominent research topic in biomedical and drug delivery applications. The versatility of their chemistry allows them to be tailored both to carry and release a wide range of active molecules, and to target specific tissues or cell types. Within a vast field of possible chemical designs, nanogels based on hyaluronic acid seem particularly interesting from the standpoint of dermatological and cosmetic applications, due to the well-known involvement of hyaluronic acid in several fundamental processes related to skin health and ageing. In spite of this, relatively few studies about these nanocarriers and their potential skin-related benefits have appeared so far in the literature. With the aim to stimulate further interest in the topic, in this review, we provide information on hyaluronic acid-based nanogels, including their key physicochemical properties, their typical drug release behavior, and the main synthetic methodologies. The latter include: approaches based on spontaneous self-assembly of polymer molecules; approaches based on chemical cross-linking, where nanogel formation is promoted by covalent bonds between polymer chains; and hybrid approaches that leverage a combination of the above two mechanisms. We believe this body of information, which we collected by going through the relevant literature from the past 10–15 years, offers cosmetic formulators plenty of options to design innovative products.